God, the universe and the last questions - García Lozano, Francisco José (Razón y fe, 2018)
Ridley Scott; Prometheus; creation; human origins; panspermia Prometheus is not Ridley Scott’s best film. His attempt to enquire cinematically about the origin of the world and the origin of the human species doesn’t seem to satisfy everyone. It is a visual and entertaining show that while embodying on the screen in an eloquently way, it tries to appear assuming.